Pengaruh Konten Kritik Instagram @Vereditum terhadap Tingkat Kepercayaan Pengikut Instagram pada Informasi Homeless Media - Christiana, Christiana; Andretty, Julian (Lembaga Yasin AlSys, 2026)
Although the phenomenon of homeless media has received attention in various studies, research that specifically discusses the influence of critical content among fellow homeless media on users’ level of trust remains limited. This study aims to analyze the influence of Instagram critical content from @vereditum on Instagram followers’ level of trust in homeless media information. This study used a quantitative approach with a survey method involving 100 respondents selected using purposive sampling. Data were collected using a closed-ended Likert-scale questionnaire, then analyzed through validity testing, reliability testing, normality testing, correlation coefficient, coefficient of determination, hypothesis testing, and simple linear regression with the assistance of SPSS software. The results showed that Instagram critical content from @vereditum had a positive and significant effect on Instagram followers’ level of trust in homeless media information. This finding was evidenced by a correlation coefficient of 0.587, indicating a moderate level of relationship, a coefficient of determination of 34.4%, and hypothesis test results showing that the calculated t-value was greater than the table t-value, namely 7.175 > 1.660, with a significance value of less than 0.05. These results align with the assumptions of online information trust theory, particularly regarding the use of cognitive heuristics in evaluating digital information. The conclusion of this study affirms the importance of critical content accompanied by verification in helping users determine their level of trust in information on social media. Practically, this study implies the need to strengthen a culture of information verification, both among homeless media managers and social media users. This study also opens opportunities for further research on other factors that influence trust in digital information.